6th International Conference on Libraries (ICOL) 2017 “Towards Lean Libraries” - Radia, Banu J. M.; Muhammad, Akmal A.; Basheer, A. Ahamadhu A. S.; Emilin, Wan W. M. A.; Shahriza, Fadly M. (Perpustakaan Hamzah Sendut, Universiti Sains Malaysia, 2018)
The International Conference on Libraries (ICOL2017) held in Penang, Malaysia on 2-3 August 2017, was the sixth international ICOL conference, a once-every-two-years opportunity that provides platform for participants and presenters to access the best information, discover new ideas and network with people in the profession. More than 20 abstracts submitted by interested authors, however, after being reviewed, only 18 papers have been accepted. Two accepted papers were withdrawn by their authors by the time of publishing. There were two speakers sponsored by the vendors who gave inputs on topics relevant to the conference but not included in this proceeding. A total of 14 full papers are included in this publication which covers the section of Managing Libraries; Creativity and Innovation; Right Tool at the Right Time and Improve while Reduce.